Superior Costal Respiration in Postoperatory Peritonitis - Gilardoni, Federico; Laviña, Raúl; Latourrette, Federico; Martínez-Apezteguía, José Luis; Pamparato, Mario; Machado, Onofre (Cirugía del Uruguay, 1980)
Among the earliest symptoms which suggest peritonitis and the first that can be detected on seeing the patient, we find superior costal respiration; its particularly valuable in those situations in which diagnosis appears difficult. In this paper the authors report three observations of postoperato·ry peritonitis of supramesocolic surface of abdomen, in which this sign was obvious at onset of complication. Diaphragmatic involvement in cases of peritonitis where the patient has reduced respiratory reserve, may lead to grave respiratory insufficiency. Reversa! of this condition can be obtained by anesthesic blocking of abdominal wall. The report of a fourth case is both demonstrative and valid far the purpose of questioning diaphragmatic contracture in peritonitis.